Analisis Strategi Pemasaran Beras Dalam Meningkatkan Penjualan : Studi Kasus : CV. Rahmat Jaya - Muhammad Abdul Aziz (Pusat riset dan Inovasi Nasional, 2023)
In 2023, the Indonesian government projects rice production of 54 million tons, while the need for rice is projected to be 32 million tons. This fact shows that the rice business is still profitable in Indonesia because rice remains the staple food that is most consumed by the community. Although wheat consumption continues to increase, rice remains the main choice. CV. Rahmat Jaya is a company that has long been engaged in the production and sale of rice. Despite facing fierce competition and market uncertainty, this company managed to manage the rice business well. CV. Rahmat Jaya is able to produce 40,000 kilograms of rice per month and sell 60,000 kilograms of rice per month. This research aims to analyze the marketing strategy carried out by CV. Rahmat Jaya in increasing sales. The research uses the SWOT Analysis approach to classify a company's position and determine marketing strategies that suit its environment. Data analysis is carried out with a SWOT matrix, which consists of strength, weakness, opportunity, and threat factors. From the results of the analysis, four alternative strategies were produced that can be considered by company management.